The Evolution of Ijtihad in Imam Khomeini's Thought and Its Effect on Selection of Leadership Successor - Saeed Shahoseini; Ghodratollah Rahmani (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2023)
One of the terms mentioned in the Iranian Constitution is "Ijtihad". For most jurists, Ijtihad means extracting sharia law from the sources of sharia, which requires mastery of sciences such as Arabic literature, logic, theology, hadith and jurisprudence. But the question that this article seeks to answer concerns Imam Khomeini’s viewpoint on this matter and its role in choosing successor leader. My basic assumption is that the concept of ijtihad in Imam Khomeini's thought has developed during the years before and after the revolution, and his late thoughts in this case, while having a significant distance from the famous theory, has a great impact in choosing successor leader. Using descriptive-analytical method, we examined the meaning and function of Ijtihad regarding the constitution as well as its definition and requirements in the works of five prominent jurists. Then, we analyzed this concept regarding Imam Khomeini's thought. Finally, we looked at his practice in choosing successor leader and the effects of his late thoughts on that.